The Relationship between Online Learning and Digital Media with Students' Academic Attitude - Muhamad Suhaimi Taat (Human Resource Management Academic Research Society, 2023)
This study was conducted to determine the relationship between online learning and digital media on students' academic attitudes. The respondents were 476 secondary government school students in the state of Sabah, Malaysia. This study used Technology Acceptance Model (TAM) as the basis of the research. Pearson Correlation analysis was performed using SPSS software to test the research’s hypotheses. The findings of the study show that there is a significant correlation between online learning (r=0.407, p=0.000) and digital media (r=0.410, p=0.000) with students' academic attitudes. The results also show that mean scores for all the variables were greater than 3.0, ranging from 3.22 to 3.95. This indicates that all variables show positive responses. Therefore, teachers should use and apply online learning and digital media efficiently and effectively in order to provide an optimal impact on students' academic attitudes.